The Layers of Composition of the Synodikon of Alexius Studites - Lauritzen, Frederick (Studia Ceranea, 2017)
The Synodikon of Orthodoxy, in its earliest version (Synodikon of Alexius Studites), has at least five different layers of composition. Beside the original one of 843/844, there is one after 845, another after 870, a fourth after 925 and finally one between 1034–1043. Since each date represents a post quem, they could be grouped together. However, the layers of composition represent different interests and objectives and therefore are difficult to conflate. On the contrary, each stratum reveals that by the 11th century the characteristic of the Synodikon was to unify different objectives and strategies into one text. It is also for this reason that the text continued to expand after Alexius Studites’ version of 1034–1043.